Fisherman Performance Anchored in Skills Work Environment and Culture: Kinerja Nelayan Berbasis Keterampilan Lingkungan Kerja dan Budaya Organisasi - Ni Komang Intan Permata Dewi; Made Dwipa Negara; Komang Sudarsana (Indonesian Journal of Law and Economics Review, 2026)
General Background Fisherman performance is important in community-based fisheries because productivity depends on technical competence, workplace conditions, and shared organizational values. Specific Background This study examined Kalisari ship fishermen who faced unstable catches, fluctuating fish prices, and coordination challenges. Knowledge Gap Prior studies mainly focused on formal organizations, while traditional fishing communities remain less explored. Aims This study analyzed the relationships between skills, work environment, organizational culture, and fisherman performance. Results Data from 33 fishermen showed that skills, work environment, and organizational culture had positive and significant partial relationships with fisherman performance. Simultaneously, the three variables were significant, with an R Square value of 0.844. Novelty This study integrates three managerial factors in a community-based maritime setting. Implications The findings support training, safer work facilities, coordination, and stronger collective values. Highlights • Technical competence showed a positive and significant partial relationship with fishing outcomes.• Safe and comfortable job conditions supported higher productivity among fishing crews.• Collective values and all tested variables explained 84.4% of outcome variation. Keywords Skills; Work Environment; Organizational Culture; Fisherman Performance; Maritime Management